Effectiveness of Student Character Education in the Digital Age of Elementary Schools: A Systematic Literature Review - Nurazizah, Vira Alya; Junaidi (Universitas Pendidikan Ganesha, 2025)
Character education at the primary school level faces significant challenges in the digital era. The widespread use of technology among children has an impact on the decline of social interaction and exposure of students to content that is not in accordance with moral and ethical values. This study aims to critically analyze the effectiveness of technology-based character education in shaping the morals of elementary school students through a Systematic Literature Review (SLR) approach. This type of research is descriptive qualitative with a systematic literature study design. The research subjects consisted of 10 scientific articles selected from 9,020 relevant publications using certain inclusion criteria. Data collection methods were carried out through documentation techniques, while the instruments used were content validity-based article selection guidelines that had been validated by experts. The data analysis technique used thematic analysis, with the process of identification, categorization, and synthesis of findings based on main themes such as the role of technology, challenges of character education, and strategies for strengthening moral values. The results showed that the wise use of technology can support character education when combined with the active role of teachers, parents and the environment. The conclusion of this study confirms that character education remains relevant and can be optimized through an adaptive digital approach. The implication is that educators and policy makers need to integrate character education strategies with digital media systematically and innovatively to adapt learning to the needs of today's generation.